2010
DOI: 10.1007/s13206-010-4412-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anti-angiogenic mechanism of HangAmDan-B (HAD-B), a Korean traditional medicine, using antibody microarray chip

Abstract: The inhibitory effects of the water extract of HangAmDan-B (WEHAD-B), which is a crude extract of eight Korean medicinal animals and plants on bFGF-induced neovascularization were investigated. WEHAD-B significantly prevented bFGF-induced HUVE cell proliferation, adhesion, migration, and capillary-like tubular network formation. Half-maximal inhibition of proliferation on the endothelial cells by WEHAD-B was observed at a concentration of approximately 250 μg/mL. Our antibody microarray-based ProteoChip data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Water extract of HAD-B was prepared by extraction of HAD-B powder with 10 times (v/w) the amount of distilled water at room temperature for 24 h. The extract was centrifuged at 1000 x g for 30 min, followed by filtering and lyophilization. The extract powder was dissolved directly in distilled water (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water extract of HAD-B was prepared by extraction of HAD-B powder with 10 times (v/w) the amount of distilled water at room temperature for 24 h. The extract was centrifuged at 1000 x g for 30 min, followed by filtering and lyophilization. The extract powder was dissolved directly in distilled water (19).…”
Section: Methodsmentioning
confidence: 99%
“…Significant prevention of basic fibroblast growth factor (bFGFs)-induced human umbilical vein endothelial (HUVE) cell proliferation, adhesion, migration, and capillarylike tubular network formation by HAD-B has recently been reported (19); however, the anti-cancer mechanisms of HAD-B have not yet been well clarified. Therefore, the present study attempted to elucidate the anti-metastatic potentials of HAD-B in human non-small cell lung cancer (NSCLC) NCI-H460 cells and the underlying intracellular signal transduction pathways involved in inhibition of metastasis.…”
Section: Inhibition Of Cell Motility and Invasion By Hangamdan-bmentioning
confidence: 99%
“…HAD-B1 was modified from the previously developed HAD-B for use as an anti-cancer herbal medicine at the East West Cancer Center (EWCC; Dunsan Korean Medicine Hospital of Daejeon University, Daejeon, Korea) (8)(9)(10). A retrospective study of HAD-B indicated it may have efficacy in treating lung cancer (11)(12)(13) and it has been demonstrated to have an anti-angiogenesis effect on HUVEC cells (14). Furthermore, HAD-B exhibited a safe toxicological profile in normal cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of HAD consisted of 9 oriental medicine herbs were proved by both in vitro and in vivo studies, and the prescription had been modified [4][5][6][7] . Furthermore, Wheel Balance Therapy (WBT), a traditional Korean medical therapy using HAD had shown positive case studies and retrospective studies on lung cancer as well [8][9][10][11][12] . The water extract of HAD (WEHAD) inhibited bFGF-induced angiogenesis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wheel Balance Therapy (WBT), a traditional Korean medical therapy using HAD had shown positive case studies and retrospective studies on lung cancer as well [8][9][10][11][12] . The water extract of HAD (WEHAD) inhibited bFGF-induced angiogenesis 12 . Slightly modified HAD, HAD-B repressed the levels of the claudin family members, and matrix metalloproteinases have been suggested as a critical target of HAD-B 13 .…”
Section: Introductionmentioning
confidence: 99%